2020
DOI: 10.1080/19476337.2020.1804463
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition, fatty acids and nutritional indices of promising freshwater fish species from Serrasalmidae family

Abstract: This study aimed to evaluate and compare the proximate composition and fatty acids (FA) profile of four fish species Piaractus mesopotamicus (PM), Colossoma macropomum (CM), Piaractus mesopotamicus X Colossoma macropomum (PC) and Piaractus brachypomus (PB). Fish fillets were analyzed for proximate composition, fatty acid profile, and nutritional quality indices. In general, PM and PB presented lower moisture content (73.75 ± 0.07 and 70.47 ± 0.16) and higher lipid content (4.34 ± 0.81 and 9.23 ± 1.16), respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Such type of associations allows in predicting wet weight and per cent water from fish body composition. A lot of work has been carried out on the analysis of moisture content of various fish species from different parts of the world (Ahmed et al, 2012; Ali et al, 2005; Ashraf et al, 2011; Breck, 2014; Chakraborty et al, 2015; Elaigwu, 2019; Farhoudi et al, 2011; Gul et al, 2017; Hadjinikolova, 2008; Hussain et al, 2011; Memon et al, 2010; Mohanty & Nayak, 2018; Njinkoue et al, 2016; Ravichandran et al, 2011; Rodrigues et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such type of associations allows in predicting wet weight and per cent water from fish body composition. A lot of work has been carried out on the analysis of moisture content of various fish species from different parts of the world (Ahmed et al, 2012; Ali et al, 2005; Ashraf et al, 2011; Breck, 2014; Chakraborty et al, 2015; Elaigwu, 2019; Farhoudi et al, 2011; Gul et al, 2017; Hadjinikolova, 2008; Hussain et al, 2011; Memon et al, 2010; Mohanty & Nayak, 2018; Njinkoue et al, 2016; Ravichandran et al, 2011; Rodrigues et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of proximate composition of three fishes from the southern Gulf of Lake Tana, Ethiopia, revealed that significantly highest value 80.50% of moisture content was recorded in C. gariepinus and the lowest value 79.00% in Oreochromis niloticus (Geremew et al, 2020). Rodrigues et al (2020) studied the proximate composition of freshwater fish species belonging to Serrasalmidae family and reported that the range of moisture amount varied from 70.47% to 79.25% in all the four fish species. The results showed that Colossoma macropomum and Piaractus mesopotamicus × C. macropomum depicted significantly higher moisture content than other two fish species while as the lowest value was significantly noted in P. brachypomus .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodrigues et al (Rodrigues et al, 2020) used GC to analyze the fatty acid profiles of 4 freshwater fish species. All samples showed a pattern where PUFA levels were greater than MUFA levels, which were greater than SFA levels.…”
Section: Discussionmentioning
confidence: 99%
“…GC‐FID analysis showed that 53 fatty acid species were identified, and the fatty acid composition of different fish varied. Rodrigues et al (Rodrigues et al., 2020 ) used GC to analyze the fatty acid profiles of 4 freshwater fish species. All samples showed a pattern where PUFA levels were greater than MUFA levels, which were greater than SFA levels.…”
Section: Discussionmentioning
confidence: 99%